(untitled) (Research, Society and Development, 2023)
Endodontic treatment is based on an understanding of the internal anatomy, which facilitates the precise exploration of the canals. The present study aimed to report a clinical case referring to the endodontic treatment of the upper left second molar, presenting the mesiopalatal canal and communication with the periodontal tissues in the distal region of the pulp chamber, in the furcation region, due to dental caries. The 41-year-old patient did not present any systemic health problems. The treatment was divided into three sessions. In the first consultation, the diagnosis of pulpal necrosis was obtained with a periapical area without changes in normality, no pain on vertical and horizontal percussion, in addition to no pain on palpation at the bottom of the sulcus and around the tooth. The radiographic examination revealed a vast region suggestive of caries in the distal region of the tooth crown, so the carious tissue was removed and the pulp chamber was accessed. In the second session, disinfectant penetration, working length determination, and instrumentation of the root canals were performed with the Reciproc R25 system for the mesiopalatal, mesiobuccal, and distobuccal canals, and R50 for the palatal canal. Bio-C Temp was used as an intracanal medication. After 18 days, the root canals were filled with apical gutta-percha cones and Bio-C Sealer, a silicate-based cement. Then, the communication in the furcation region was sealed with the repair cement, Biodentine. The pulp chamber floor was sealed with light-curing glass ionomer, and the pulp chamber was filled with composite resin.